ENGINEERING-GEOLOGICAL ZONING FOR DETECTION OF POSSIBLE AREAS OF HAZARDOUS PROCESSES BASED GEOLOGICAL GIS AND CARTOGRAPHIC MODELING - Dyniak, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Violation of the stability of the geological environment activates the development of dangerous geological processes. One of the most challenging and common processes in urban areas are flooded by groundwater. The above possibility and feasibility of cartographic modeling and GIS to study processes of underflooding.